Drug Repurposing for Targeting Acute Leukemia With KMT2A (MLL)—Gene Rearrangements - Tsakaneli, Alexia; Williams, Owen (Frontiers in Pharmacology, 2021)
The treatment failure rates of acute leukemia with rearrangements of the Mixed Lineage Leukemia (MLL) gene highlight the need for novel therapeutic approaches. Taking into consideration the limitations of the current therapies and the advantages of novel strategies for drug discovery, drug repurposing offers valuable opportunities to identify treatments and develop therapeutic approaches quickly and effectively for acute leukemia with MLL-rearrangements. These approaches are complimentary to de novo drug discovery and have taken advantage of increased knowledge of the mechanistic basis of MLL-fusion protein complex function as well as refined drug repurposing screens. Despite the vast number of different leukemia associated MLL-rearrangements, the existence of common core oncogenic pathways holds the promise that many such therapies will be broadly applicable to MLL-rearranged leukemia as a whole.